Quantifying services and disservices provided by insects and vertebrates in cacao agroforestry landscapes - Vansynghel, Justine; Ocampo-Ariza, Carolina; Maas, Bea; Martin, Emily A.; Thomas, Evert; Hanf-Dressler, Tara; Schumacher, Nils-Christian; Ulloque-Samatelo, Carlos; Yovera, Fredy F.; Tscharntke, Teja; Steffan-dewenter, Ingolf (Royal Society, 2022)
Animals provide services such as pollination and pest control in cacao agro- forestry systems, but also disservices. Yet, their combined contributions to crop yield and fruit loss are mostly unclear. In a full-factorial field exper- iment in northwestern Peru, we excluded flying insects, ants, birds and bats from cacao trees and assessed several productivity indicators. We quan- tified the contribution of each group to fruit set, fruit loss and marketable yield and evaluated how forest distance and canopy closure affected pro- ductivity. Fruit set dropped (from 1.7% to 0.3%) when flying insects were excluded and tripled at intermediate (40%) compared to high (greater than 80%) canopy cover in the non-exclusion treatment. Fruit set also dropped with bird and bat exclusion, potentially due to increased abundances of arthropods preying on pollinators or flower herbivores. Overall, cacao yields more than doubled when birds and bats had access to trees. Ants were generally associated with fruit loss, but also with yield increases in agroforests close to forest. We also evidenced disservices generated by squir- rels, leading to significant fruit losses. Our findings show that several functional groups contribute to high cacao yield, while trade-offs between services and disservices need to be integrated in local and landscape-scale sustainable cacao agroforestry management